2010
DOI: 10.1021/ef100797h
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Inclusion of Dispersion in the Modeling of Asphaltene Dimers

Abstract: Modeling of asphaltenes presents many challenges, not least of which is their large size and the lack of definitive experimental structure information. However, a further fundamental issue of importance is the ability of the modeling methodology to accurately predict noncovalent interactions, particularly dispersion (London) forces. The self-aggregation properties of asphaltenes are primarily driven by such interactions. Therefore, for a modeling approach to be insightful, dispersion must be accounted for. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
(78 reference statements)
2
10
0
Order By: Relevance
“…To accurately describe p-stacking interactions, as well as to emphasize the importance of dispersion energy as a key factor in stabilizing the stacked dimers, dispersion-corrected DFT functional, B97-D [43], associated with basis sets 6-31G ⁄ and 6-311+G ⁄⁄ , was selected as the level of DF calculations to optimize the structures. Recently, B97-D has been widely used to describe macro structures like asphaltene sheets and DNA-base pairs [44][45][46][47][48] Counterpoise (CP) correction [49,50] was performed to limit basis set superposition error (BSSE) while studying intermolecular interactions.…”
Section: Methodsmentioning
confidence: 99%
“…To accurately describe p-stacking interactions, as well as to emphasize the importance of dispersion energy as a key factor in stabilizing the stacked dimers, dispersion-corrected DFT functional, B97-D [43], associated with basis sets 6-31G ⁄ and 6-311+G ⁄⁄ , was selected as the level of DF calculations to optimize the structures. Recently, B97-D has been widely used to describe macro structures like asphaltene sheets and DNA-base pairs [44][45][46][47][48] Counterpoise (CP) correction [49,50] was performed to limit basis set superposition error (BSSE) while studying intermolecular interactions.…”
Section: Methodsmentioning
confidence: 99%
“…However, in their standard implementation, they are not capable of taking into account dispersion effects in weakly bound complexes. To correct these deficiencies, DFT–vdW- and DFT–dispersion-corrected approaches have appeared recently in the literature . It is worth noting that standard DFT families, such as BLYP and B3LYP, are only able to give repulsive dimeric interactions, whereas PW91 pure functional is able to give a correct description of the intermolecular potential for a great variety of molecular dimers. , In this context, we have recently demonstrated that this particular functional gives a good description for σ–π and π–π interactions in a series of heteroaromatic monocyclic molecular complexes of benzene, pyridine, and thiophene molecules, where the binding energies are compared to results obtained with more sophisticated methods, such as MP4 and CCSD.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, asphaltene systems have often been represented as a mixture of various (often three) structures with different sizes and characteristics, and that can be considered individually as asphaltene molecules [9][10][11][12].…”
Section: Modelmentioning
confidence: 99%